Subtropical Dry Forests: The Main Forest Ecoregion of Argentina - Verga, Anibal (2020)
The Chaco is a sparsely populated, wooded grassland natural region of the Río de la Plata basin, where four physiognomic regions can be identified: Humid Chaco, Semi-arid Chaco, Arid Chaco, and Chaco Serrano. In this introduction to the section of subtropical dry forests, the most relevant tree genera and species are presented. A severe degradation and deforestation process characterize this region in the current century. The main productive systems are described, together with their effects on environmental, economic, and social aspects: extraction of firewood, production of charcoal, and extensive livestock. The recent advance of the agricultural frontier threatens the native communities living within and from the forest in an ancient equilibrium: changes in land use, technological advances of agriculture, increase of logging in the natural forest are occurring. A new tree-centered production paradigm is needed. “Quebracho” species represent a historical paradigm of overexploitation but a promise of possible sustainable management. Key species for the reconversion of the productive systems in the Chaco (not treated in the following chapters) are presented, taking into account their potential for breeding and relevance for restoration, within the environmental, economic, and social context of the region.